Triple-Fortified Rice Containing Vitamin A Reduced Marginal Vitamin A Deficiency and Increased Vitamin A Liver Stores in School-Aged Thai Children. Issue 4 (5th February 2014) - Pinkaew, Siwaporn; Wegmuller, Rita; Wasantwisut, Emorn; Winichagoon, Pattanee; Hurrell, Richard F.; Tanumihardjo, Sherry A.
Abstract: Vitamin A (VA)-fortified rice is a potential intervention strategy to prevent VA deficiency in at-risk populations. Hot-extruded, triple-fortified rice grains with added VA, zinc, and iron were produced by hot extrusion technology and their ability to improve VA status was tested in Thai schoolchildren. The fortification levels were 10 mg of iron, 9 mg of zinc, and 1.05 mg of VA/g extruded rice. A paired stable isotope dilution technique with labeled 13 C2 -retinyl acetate ( 13 C-RID) was used to quantify VA pool size at the beginning and end of the feeding period. Fifty healthy schoolchildren with a serum retinol (SR) concentration of >0.7 μ mol/L were randomly assigned to 2 groups to receive either triple-fortified rice ( n = 25) or natural rice ( n = 25) for 2 mo as part of the daily school meal. The fortified grains, mixed 1:50 with regular rice, were estimated to provide an extra 890 μ g of VA/d, 5 d/wk. 13 C2 -retinyl acetate (1.0 μ mol) was administered orally to each child before and at the end of the feeding period to estimate total body reserves (TBRs) of VA, which increased significantly ( P < 0.05) in the intervention group from 153 ± 66 μ mol retinol at baseline to 269 ± 148 μ mol retinol after 2 mo of feeding. There was no change in the TBRs of VA in the control group (108 ± 67 vs. 124 ± 89 μ mol retinol) ( P = 0.22). Serum retinol remained unchanged in both groups. We conclude that VA-fortified, hot-extruded rice is an efficacious vehicle to provide additional VA to at-risk populations, and that the efficacy of VA-fortified foods can be usefully monitored by the 13 C-RID measurement of TBRs of VA but not by changes in SR concentration. This trial was registered at clinicaltrials.gov as NCT01199445.